2020
DOI: 10.1097/ico.0000000000002589
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids Versus Cyclosporine for Subepithelial Infiltrates Secondary to Epidemic Keratoconjunctivitis: A Prospective Randomized Double-Blind Study

Abstract: Purpose: To compare efficiency and tolerance between topical 0.5% cyclosporine A (CSA) and fluorometholone (FML) for subepithelial infiltrates (SEI) complicating epidemic keratoconjunctivitis. Methods:We conducted a prospective double-blind randomized study involving 72 eyes with SEI. Thirty-eight eyes were treated with topical FML (FML group) and 34 eyes with CSA 0.5% eye drops (CSA group). Treatment was considered successful in case of SEI reduction and visual acuity improvement. Tolerance was evaluated by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Another trial that randomized participants with SEIs to a 6-month course of either fluorometholone or 0.5% cyclosporine found that SEIs were more likely to resolve in the steroid group at 3 months (39% vs. 13%) and 6 months (70% vs. 47%), although with wide CIs. 62 Recurrence of SEIs 1 month after discontinuation of therapy was observed in 16% of the steroid group and 9% of the cyclosporine group. Thus, although the role of topical steroids for EKC has not been fully established, trials have not consistently found a benefit for preventing SEIs when used in acute EKC.…”
Section: Viral Keratitismentioning
confidence: 94%
“…Another trial that randomized participants with SEIs to a 6-month course of either fluorometholone or 0.5% cyclosporine found that SEIs were more likely to resolve in the steroid group at 3 months (39% vs. 13%) and 6 months (70% vs. 47%), although with wide CIs. 62 Recurrence of SEIs 1 month after discontinuation of therapy was observed in 16% of the steroid group and 9% of the cyclosporine group. Thus, although the role of topical steroids for EKC has not been fully established, trials have not consistently found a benefit for preventing SEIs when used in acute EKC.…”
Section: Viral Keratitismentioning
confidence: 94%